Pharmacological Evaluation of F45 on the Cardiovascular System Using In Vitro, In Vivo Models and Molecular Dockings - Abdurazakova, Ikbolkhon; Zaynabiddinov, Anvar; Abdullaev, Izzatullo; Makhmudov, Lazizbek; Gayibov, Ulugbek; Omonturdiev, Sirojiddin; Abdullayev, Gafurjon; Xolmirzayeva, Madina; Zhurakulov, Sherzod (Trends in Sciences, 2025)
The current study investigated the vasorelaxant and antihypertensive potential of the novel compound F-45 through a combination of in vitro, in vivo, and in silico approaches. F-45 demonstrated significant relaxation of rat aortic rings pre-contracted with KCl and phenylephrine, suggesting its capacity to inhibit both voltage-dependent L-type Ca2+ channels and receptor-operated calcium entry mechanisms. At 70 μM, F-45 reduced KCl-induced contraction by 84.0% ± 1.3%, while 45 μM of F-45 inhibited phenylephrine-induced contraction by 78.0% ± 2.2%. Endothelium-denuded experiments confirmed that nitric oxide signaling contributes significantly to F-45-mediated vasorelaxation, with a 35.0% ± 2.4% reduction in relaxation observed after endothelial removal. Molecular docking studies revealed high binding affinities of F-45 for Ca2+-ATPase (−8.6 kcal/mol) and Sodium\Calcium Exchanger (−6.8 kcal/mol), supporting its role in modulating calcium transport. In vivo experiments using tail-cuff plethysmography showed that 50 mg/kg of F-45 reduced SBP and DBP from 132.5 ± 12.3 and 94.3 ± 9.1 to 96.8 ± 9.4 and 65.3 ± 6.4 mmHg, respectively. In the adrenaline-induced hypertension model, F-45 decreased elevated SBP and DBP from 140.8 ± 14.2 and 104.3 ± 10.3 to 90.0 ± 8.7 and 61.5 ± 6.0 mmHg within 2 h. These findings suggested that F-45 is a promising candidate for further development as a natural antihypertensive agent with multimodal action. HIGHLIGHTS F45 demonstrated potent vasorelaxant activity in isolated rat aortic rings, primarily through inhibition of L-type and receptor-operated calcium channels. Endothelium-dependent mechanisms, especially nitric oxide (NO) signaling, significantly contributed to the vascular relaxation induced by F-45. Molecular docking analysis revealed high binding affinities of F-45 to Ca2+-ATPase (−8.6 kcal/mol) and NCX (−6.8 kcal/mol), supporting its role in calcium homeostasis modulation. In vivo experiments confirmed a dose-dependent antihypertensive effect, with 50 mg/kg of F-45 significantly reducing systolic and diastolic blood pressure. In an adrenaline-induced hypertension model, F-45 rapidly normalized elevated blood pressure, suggesting its potential as a fast-acting antihypertensive agent. GRAPHICAL ABSTRACT